Smile Dental Program : Pendidikan Kesehatan Tentang Cara Menyikat Gigi yang Baik dan Benar - Debby Yulianthi Maria (Humanism: Journal of Community Empowerment (HJCE), 2020)
Tooth decay is still a serious health problem in Indonesia. Dental health education is important to do early to avoid damage to his teeth. Dental health education must be made attractive, attractive, without reducing its contents. Education is carried out using audio-visual programs and also through direct demonstrations. This community service activity aims to provide education about how to brush teeth well and correctly so that students of the Al Munawwaroh Sewon Bantul TPA Mosque know and can get used to maintaining their dental health.TPA students are at the elementary school age, which is ideal for practicing children's motor skills, one of which is brushing their teeth. The results of community service activities with the theme of the smile dental program: health education about how to brush teeth properly and correctly can be concluded to be interesting and have an influence to change children's behavior for the better in terms of dental care, so this activity must be given repeatedly and requires collaboration between students, parents and teachers.